SURVEY OF TOOLS AND TECHNOLOGIES FOR PSYCHOEMOTIONAL SCREENING AND DETERMINING THE STATUS OF PATIENTS WITH DEPRESSION - PYTLYAK, Maksym (Computer systems and information technologies, 2026)
The article is devoted to a comprehensive analysis of the current state and prospects for the development of information technologies for psychoemotional screening of patients with depressive disorders. The relevance of the study is due to the global increase in the prevalence of mental disorders, which in the conditions of modern challenges, in particular martial law, is becoming a critical threat to public health and economic stability. The work systematizes scientific sources, which made it possible to identify key trends in the field of digital psychiatry. The main attention is paid to a comparative analysis of existing methods according to eight fundamental criteria that determine the suitability of the technology for real clinical implementation. Among them, the availability of decision-making algorithms, patient routing mechanisms in the primary care setting, the use of validated psychometric tools, integration with electronic medical records, real-time notification systems, adaptation to the individual user norm, ethical transparency, and research on objective behavioral markers. The results of the analysis indicate a significant fragmentation of existing solutions - with a high interest of researchers in the use of biomarkers (voice, eye tracking, electroencephalography and locomotor activity) and artificial intelligence, there is an almost complete absence of systems integrated into the state medical infrastructure. It was found that most of the existing mobile applications and cyber-physical systems operate in isolation from the primary care level, which complicates timely diagnostics and continuity of treatment. The work places special emphasis on the importance of digital phenotyping, which allows objectifying the patient's condition through monitoring motor activity, but it is proven that such data must necessarily be combined with classical clinical protocols. It is substantiated that the lack of integration with electronic medical records and formalized routing algorithms are the main barriers to creating an effective national screening system. Based on the identified "blank spots" in world scientific practice, the author has proven the need to develop a unified information technology that would act as a full-fledged link in the medical process. The analytical basis of the article serves as a theoretical basis for designing a new information technology capable of providing a closed cycle of "monitoring - diagnostics - routing - treatment". The scientific novelty of the work lies in the systematic approach to evaluating screening technologies, which allows us to clearly identify the vectors of further research in the direction of creating information technology adapted to the needs of the modern healthcare system.